2018
DOI: 10.3130/aijs.83.1423
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Strategy of Hysteretic Mass Damper for Reducing Inter-Story Drift Beyond Elastic Limit of Steel Buildings

Abstract: This paper discusses hysteretic tuned mass dampers (TMDs), which could passively be tuned according to the change of the degree of nonlinearity in steel buildings during earthquakes. Design properties for TMDs are composed of strength, stiffness and post-yielding stiffness. Optimal values for these properties are analyzed through stochastic analysis and closed forms of the optimal values are formulated. Finally, an estimation method for the peak displacement of buildings is proposed based on equivalent lineari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…12,13 The response reduction effects of a hysteretic TMD system incorporated into the top of a building model under seismic excitations have been studied. 14 A seismic retrofitting using large TMDs with a total weight exceeding 5% of the effective building weight was applied to an existing tall building. 15 A seismic mass damper system using scrap tire pads was proposed, dynamic loading tests on a tire rubber pads unit were conducted, and the control effect of a building structure was numerically evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 The response reduction effects of a hysteretic TMD system incorporated into the top of a building model under seismic excitations have been studied. 14 A seismic retrofitting using large TMDs with a total weight exceeding 5% of the effective building weight was applied to an existing tall building. 15 A seismic mass damper system using scrap tire pads was proposed, dynamic loading tests on a tire rubber pads unit were conducted, and the control effect of a building structure was numerically evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…In these cases, ignoring bending deformation would lead to an incorrect evaluation of dynamic behaviors and, thus, may invalidate the seismic control measures. But so far, only a few studies can be found specifically on bending influences on seismic performance, i.e.,: Kaneko [ 8 ] employed a lumped mass stick model with shear springs and rotational springs to take into account the overall bending deformation of a structure, and then deduced an optimal damping and equivalent stiffness of the TMD. Ping et al [ 9 ] integrated an optimum TMD into the shear-bending building and performed different control methods to examine the control efficiency.…”
Section: Introductionmentioning
confidence: 99%